A family with juvenile polyposis linked to the BMPR1A locus: cryptic mutation or closely linked gene? - Chow, E; Lipton, L; Carvajal-Carmona, L; Arthur, G; Bhathal, P; Kaur, G; Jaeger, E; Woodford-Richens, K; Howarth, K; Tomlinson, I; Macrae, F (Blackwell Publishing, 2007)
BACKGROUND AND AIM: Familial juvenile polyposis syndrome (JPS) is a rare autosomal dominant condition in which patients develop hamartomatous gastrointestinal polyps with malignant potential. Pathogenic germline mutations in both the SMAD4 and BMPR1A genes involved in the transforming growth factor beta pathway account for 40% of cases of JPS. Genetic heterogeneity remains evident, as the balance of cases is not accounted for by mutations in these genes. The aim of this study was to determine the mutation responsible in a family with juvenile polyposis. METHODS: An Australian Caucasian family with juvenile polyposis have attended and followed surveillance plans through the Familial Bowel Cancer Clinic, The Royal Melbourne Hospital. A pedigree of the family was constructed with attention to the mixed phenotypic expression of polyps in affected members. Genetic testing for SMAD4 and BMPR1A mutations in germline DNA and linkage analysis to SMAD4, BMPR1A and 15q14 (CRAC1 locus) were performed. RESULTS: There were no pathogenic mutations in SMAD4 and BMPR1A. There was no linkage to SMAD4 or 15q14 (CRAC1 locus). Linkage analysis suggested a cryptic BMPR1A mutation or the presence of another gene in close proximity to the BMPR1A locus. Two additional candidate genes in the region of linkage (PTEN and MINPP1) were excluded. CONCLUSION: Most affected members of this Australian Caucasian family demonstrate a phenotype of mixed polyps: juvenile polyps, adenomas and/or hyperplastic polyps. Cloning of a potentially responsible gene closely linked to the BMPR1A locus or a cryptic mutation in BMPR1A may offer valuable insights into the pathogenesis of JPS.